Comparison of surface macrotexture measurement methods - Fisco, Nicholas; Sezen, Halil (Journal of Civil Engineering and Management, 2014)
Recent advances in technology allowed for the use of laser-based systems that can directly measure macrotexture properties of various surfaces. Volumetric or sand patch method has historically been used as the main technique for measuring macrotexture. Different available methods do not all measure the same surface properties and often generate different measurements. Thus, it is crucial to determine the most suitable method for measuring surface macrotexture. This paper investigates mean profile depth measurements from three laser based macrotexture measuring devices, including a laser profiler, a laser texture scanner and a circular texture meter. The results are compared with mean texture depth obtained from volumetric sand patch tests. Experiments were conducted to measure macrotexture of 26 laboratory specimens, which included asphalt and Portland cement concrete samples of various type and finish, as well as other common manufactured textured samples. Based on the evaluation of experimental data collected in this study, relationships are recommended to predict standard macrotexture using the mean profile depth data measured by a laser equipment or scanner.